The rich palette of the economic history curriculum. Issue 2 (24th March 2022) - Fishback, Price; Haupert, Michael
Abstract: Teaching economic history requires the study of how to combine the economists' modeling and statistical methods with the methods used by historians and the other social sciences. It often involves learning how to search for quantitative data from a variety of sources and then building panel datasets that match the data found with existing datasets. Economic historians also must work with narrative sources to develop an understanding of the historical context and the political, social, and economic institutions that influence the research questions. In some settings, the analysis focuses fully on narrative evidence because it is the only material available. While modern studies are restricted because the future is unknown, economic history can examine issues in the short, intermediate, and long run. Economic history provides a rich palette for educating undergraduate students in economics and the social sciences. The field is even more interdisciplinary than the wedding of history and economics. In 1978, Nobel Laureate Douglass North described its task as the study of the performance and structure of economies through time. North's research agenda over the rest of his career combined politics, religion, perceptions, ideologies, the sociology of knowledge, and a variety of topics studied by scholars throughout the social sciences.